Case report: successful treatment of refractory SAPHO syndrome with the JAK inhibitor tofacitinib. Issue 25 (June 2018) - Yang, Qiao; Zhao, Yumo; Li, Chen; Luo, Yaping; Hao, Weixin; Zhang, Wen
Abstract: Introduction: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is an autoinflammatory disorder without standardized treatment. Janus kinase (JAK) inhibitors can block a range of cytokines and might possess significant anti-inflammatory activity. Here, we report the first case of efficacious treatment of refractory SAPHO syndrome with the JAK inhibitor tofacitinib. Case presentation: A 44-year-old woman presented with arthralgia in the right wrist and complained of having difficulty in doing housework. Symptoms were unresponsiveness to nonsteroidal anti-inflammatory drugs, disease-modifying antirheumatic drugs, and tumor necrosis factor inhibitors. A diagnosis of SAPHO syndrome was made based on previous dermatological and osteoarticular manifestations and bone scintigraphy findings. Oral treatment with tofacitinib at 5 mg twice daily in combination with the basic methotrexate treatment was initiated. After 4 weeks of using tofacitinib, the patient reported marked improvement of symptoms and also reported being competent in completing housework. Conclusions: The efficacy of JAK inhibitors in treating refractory SAPHO syndrome should be noted.